2017
DOI: 10.1016/j.eucr.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Non-ascitic Peritoneal Carcinomatosis from Metastatic Prostate Cancer

Abstract: Prostate cancer most commonly metastasizes to bone, lung and liver. Omental metastasis of prostate cancer is extremely rare, with only a few cases reported in the literature, many of which have associated ascites. We present a case of non-ascitic omental metastasis of prostate cancer without any bone metastases. Furthermore, this patient has had two negative measurements of circulating tumor cells (CTCs) in the blood, suggesting a non-hematogenous route of metastasis to the omentum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…In reviewed MCRPC cases, chemotherapeutic agents (such as Docetaxel) and corticosteroids had some impact on the extent of peritoneal disease. Also, Sheng et al 5 reported the case of a 60 year-old male who underwent total omentectomy, with a subsequent drop in PSA from 11.8 to 1.8 ng/ml. This patient then had a rise in PSA and recurrence of peritoneal nodules, which responded well to ADT.…”
Section: Discussionmentioning
confidence: 99%
“…In reviewed MCRPC cases, chemotherapeutic agents (such as Docetaxel) and corticosteroids had some impact on the extent of peritoneal disease. Also, Sheng et al 5 reported the case of a 60 year-old male who underwent total omentectomy, with a subsequent drop in PSA from 11.8 to 1.8 ng/ml. This patient then had a rise in PSA and recurrence of peritoneal nodules, which responded well to ADT.…”
Section: Discussionmentioning
confidence: 99%
“…We are the first to report two cases of metastatic peritoneal carcinomatosis of prostate cancer from a high-volume single institution. Table 1 compares our cases to previous cases from the literature (1,2,3,4,5,6,7,8,9,10,11). Our cases are unique in several ways.…”
Section: Discussionmentioning
confidence: 92%
“…Peritoneal carcinomatosis from prostate cancer, with and without evidence of other metastatic sites, is extremely rare and not well studied. A handful of case reports describe dissemination at the time of cancer diagnosis as well as after treatment (1,2,3,4,5,6). These presentations vary widely, with most patients presenting with new-onset malignant ascites.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate adenocarcinoma metastasizes in 35% of cases after radical prostatectomy, the bones being the most targeted organ (90%). 4 It is known that it can metastasizes elsewhere as in the lung, the liver or even in the peritoneum. 4 Nonetheless, peritoneal dissemination without any other organ involved especially the bone is very rare.…”
Section: Discussionmentioning
confidence: 99%
“… 4 It is known that it can metastasizes elsewhere as in the lung, the liver or even in the peritoneum. 4 Nonetheless, peritoneal dissemination without any other organ involved especially the bone is very rare. In fact, only 7 cases of histologically-proven peritoneal metastases following laparoscopic surgery, whether robot-assisted or not, are reported in the literature in the absence of other metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%